The Application of Cohesion and Translation Strategy in the Holy Quran: Arabic and English in Contrast - Mardani, Tooba; Sadeqi, Muhammad (LANGUAGE ART, 2022)
The present study focuses on cohesive devices in terms of frequency rate. In doing so, the surah of “Bacara” has been contrastively compared with its English rendering version. The Arabic text of the holy Quran was selected as a source text and the English translation as a target text. Cohesive devises were reference, ellipsis, conjunction, substitution, and lexical markers. The religious texts are sensitive, and that’s why they were broadly identified along with their subcomponents both in the ST (source text) to the TT (target text), then counted and compared. The study employs descriptive qualitative methodology and describes the specific cohesion relations in every sentence, so the model of Halliday and Hassan’s (1976) followed. In summary, the result obviously confirms that the comparison of the frequency of each component of cohesive devises between the original Arabic text and the English rendering has some differences and discrepancies in strategy and application by the translator.